Fiber Bragg Grating Thermometry and Post-Treatment Ablation Size Analysis of Radiofrequency Thermal Ablation on Ex Vivo Liver, Kidney and Lung - Sanzhar Korganbayev; Leonardo Bianchi; Clara Girgi; Elva Vergantino; Domiziana Santucci; Eliodoro Faiella; Paola Saccomandi (Sensors)
Radiofrequency ablation (RFA) is a minimally invasive procedure that utilizes localized heat to treat tumors by inducing localized tissue thermal damage. The present study aimed to evaluate the temperature evolution and spatial distribution, ablation size, and reproducibility of ablation zones in ex vivo liver, kidney, and lung using a commercial device, i.e., Dophi™ R150E RFA system (Surgnova, Beijing, China), and to compare the results with the manufacturer’s specifications. Optical fibers embedding arrays of fiber Bragg grating (FBG) sensors, characterized by 0.1 °C accuracy and 1.2 mm spatial resolution, were employed for thermometry during the procedures. Experiments were conducted for all the organs in two different configurations: single-electrode (200 W for 12 min) and double-electrode (200 W for 9 min). Results demonstrated consistent and reproducible ablation zones across all organ types, with variations in temperature distribution and ablation size influenced by tissue characteristics and RFA settings. Higher temperatures were achieved in the liver; conversely, the lung exhibited the smallest ablation zone and the lowest maximum temperatures. The study found that using two electrodes for 9 min produced larger, more rounded ablation areas compared to a single electrode for 12 min. Our findings support the efficacy of the RFA system and highlight the need for tailored RFA parameters based on organ type and tumor properties. This research provides insights into the characterization of RFA systems for optimizing RFA techniques and underscores the importance of accurate thermometry and precise procedural planning to enhance clinical outcomes.